Factors associated with persistent post-concussion symptoms following mild traumatic brain injury in adults - Ponsford, Jennie (2020)
Objectives: Debate regarding factors associated with persistent symptoms following mild traumatic brain injury continues. Nested within a trial aiming to change practice in emergency department management of mild traumatic brain injury, this study investigated the nature of persistent symptoms, work/study outcomes, anxiety and quality of life and factors associated with persistent symptoms following injury, including the impact of receiving information about mild traumatic brain injuries in the emergency department. Methods: A total of 343 individuals with mild traumatic brain injury completed the Rivermead Post-Concussion Symptom Questionnaire, Hospital Anxiety Depression Scale – Anxiety Scale, and Quality of Life – Short Form in average 7 months post-injury. Results: Overall, 18.7% of participants reported 3 or more post-concussional symptoms, most commonly fatigue (17.2%) and forgetfulness (14.6%). Clinically significant anxiety was reported by 12.8%, and was significantly associated with symptom reporting, as were mental and physical quality of life scores. Significant predictors of post-concussional symptoms at follow-up were pre-injury psychological issues, experiencing loss of consciousness, and having no recall of receiving information about brain injury in the emergency department. Conclusion: This study confirms that loss of consciousness and pre-injury psychological issues are associated with persistent symptom reporting. Not receiving injury information in the emergency department may also negatively influence symptom reporting.